Baseline Conservative and Surgical Management in the Treatment of NSAID-Exacerbated Respiratory Disease - Sillanpää, Saara; Numminen, Jura (Frontiers in Allergy, 2021)
Nonsteroidal anti-inflammatory drug (NSAID)-exacerbated respiratory disease (N-ERD) is a chronic medical condition that includes asthma, chronic rhinosinusitis with nasal polyposis, and hypersensitivity to aspirin and other NSAIDs. Eosinophilic inflammation in the upper and lower airways is treated with local corticosteroids, repeated antibiotics, oral corticosteroid courses, endoscopic sinus surgery, and in some cases aspirin treatment after desensitization (ATAD). Nevertheless, the disease may be uncontrolled and it has a great impact on quality of life. A better understanding of the pathomechanisms of the disease and the development of medications that target type 2 inflammation mediators may have a crucial role in achieving better disease control in patients with N-ERD.